Effects of Waste Glass Powder on the Geotechnical Properties of Loose Subsoils - Siyab Khan, Muhammad; Tufail, Muhammad; Mateeullah, Mateeullah (Civil Engineering Journal, 2018)
Foundation soils are most affected by different problems when it comes to the loose soil having low shear strength and bearing capacity. Failure of the soil with settlement and shear arises when the shear stresses in the soil exceed the limit. This study is keen to observe the effects of utilization of waste broken glass in the enhancement of Geotechnical properties of soil by performing different laboratory tests. Collection of the soil sample from was concluded from Pabbi, Peshawar, KPK, and Pakistan, which is a low strength soil, are also being called soft soil having low bearing capacity. Furthermore, this particular soil was needed to be enhanced. The physical, chemical and engineering properties of virgin soil were contemplated and the soil was treated with added substances of Glass Powder to stabilize the local soil. Addition of Glass Powder was finished in different proportions that are 4%, 8% and 12% etc. Performance of different tests as Gradation, Specific Gravity, Standard Proctor compaction, Atterberg Limits, Direct Shear, CBR and so forth were done. The results were concluded, based on the Glass Dust stabilization analysis. It was obtained that pulverized glass can be effectively used as a soil stabilizer as mainly the strength characteristics were observed to be valeted. The Results showed that the gradation of soil is narrow from the particle size analysis. Plasticity index (P.I), Liquid limit (L.L) and plastic limit (P.L) were decreased with the addition of Glass powder. The reason behind decreasing P.I is maybe the fact that the Glass powder is cohesionless. Ideal percentage of Glass Powder as a stabilizer is 8%. Such improvements included an achievement of the highest CBR obtained at the 4%, 8% and 12% of powdered glass content. The reason is that the glass is pozzolanic material when blended with soil gives additional strength. The achievement of the increasing rate of the values of angle of internal friction on 4% and 8% and decreasing rate of values obtained at 12% powdered glass substances. Cohesion rate decreases up to 8% and starts increasing at 12%. Maximum dry density increasing as the density of glass is higher than such soil and Optimum moisture content (OMC) is decreasing because of low absorption capacity of glass. The study showed that the best stabilizer for the case study (Pabbi, Peshawar) is the Glass Powder and the optimum dose is 8 %.